Livres muets - Martine Créac’h (Appareil)
In the history of art, the book is often presented as a writing medium offered for reading. But how can a book become a work of art when it is displayed as a mute object ? I would like to answer this question by examining the strange literary and plastic fortune of an engraving by Hercules Seghers, produced between 1618 and 1622.At the center of the engraving are three untitled books. The spines of the bindings and the covers are hidden. Only one page is visible but it is illegible. Known as “Les trois livres”, “Pile de livres” or “Nature morte aux livres”, this engraving is therefore considered a still life, and even the very first still life in European graphic art. However, the arrangement of the three books, and the way the stack is constituted, suggest interrupted reading.Also a poet and publisher, Pierre Lecuire (1922-2013) dreamed of creating a “Tombeau d’Hercules Seghers” with Nicolas de Staël. The project leads to a collective work based on Seghers engravings by contemporary artists, painters and engravers in Le Livre des livres I (1974), accompanied by musicians in Le Livre des livres II (1982). Lecuire takes part in the work as a poet, but also as an editor, building an architecture for these works. It is not the message of the books that inspires him, but rather their formal characteristics.Returning to Nicolas de Staël’s annotations and drawings, the poet André du Bouchet (1924-2001) reflects on the action of Staël’s stroke on Seghers’ line, reversing the orientation of time to make Staël’s work the origin of that of Seghers. In the pages he himself devoted to the engraver, the silent pages become geological strata.